Definition and Prioritization of Data Elements for Cohort Studies and Clinical Trials on Patients with Unruptured Intracranial Aneurysms: Proposal of a Multidisciplinary Research Group - Hackenberg, Katharina A. M.; Algra, Ale; Al-Shahi Salman, Rustam; Frösen, Juhana; Hasan, David; Juvela, Seppo; Langer, David; Meyers, Philip; Morita, Akio; Rinkel, Gabriel; Etminan, Nima (Neurocritical care, 2019)
Introduction Variability in usage and definition of data characteristics in previous cohort studies on unruptured intracranial aneurysms (UIA) complicated pooling and proper interpretation of these data. The aim of the National Institute of Health/National Institute of Neurological Disorders and Stroke UIA and Subarachnoid Hemorrhage (SAH) Common Data Elements (CDE) Project was to provide a common structure for data collection in future research on UIA and SAH. Methods This paper describes the development and summarization of the recommendations of the working groups (WGs) on UIAs, which consisted of an international and multidisciplinary panel of cerebrovascular specialists on research and treatment of UIAs. Consensus recommendations were developed by review of previously published CDEs for other neurological diseases and the literature on UIAs. Recommendations for CDEs were classified by priority into ‘Core,’ ‘Supplemental—Highly Recommended,’ ‘Supplemental,’ and ‘Exploratory.’ Results Ninety-one CDEs were compiled; 69 were newly created and 22 were existing CDEs. The CDEs were assigned to eight subcategories and were classified as Core (8), Supplemental—Highly Recommended (23), Supplemental (25), and Exploratory (35) elements. Additionally, the WG developed and agreed on a classification for aneurysm morphology. Conclusion The proposed CDEs have been distilled from a broad pool of characteristics, measures, or outcomes. The usage of these CDEs will facilitate pooling of data from cohort studies or clinical trials on patients with UIAs.